That thing about Bollywood - Kelkar, Supriya, 1980- (Simon & Schuster Books for Young Readers, 2022)
Middle-schooler Sonali cannot bring herself to share her feelings, but when she wakes up one day and begins to involuntarily burst into Bollywood song and dance routines that showcase her emotions, she realizes she has to find her voice and share her feelings.